Assesment Kemampuan Membaca Kelas Remdah Pada Anak Disleksia Di SDN Pondok Bahar 03 - Septy Nur Fadillah; Putra Fauzan Moh Wildan; Galang Al Ayubi; Muhammad Fahmi (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Inclusive education requires learning services that can accommodate the diversity of student abilities, including children with reading difficulties such as dyslexia. A common problem in elementary schools that provide inclusive education is the low initial reading ability of students with special needs in lower grades. This study aims to describe the implementation of initial reading instruction in the con⅔text of inclusive education and identify the obstacles experienced by students with dyslexia. This study uses a qualitative approach with a case study type. The research subjects included early grade elementary school students, class teachers, students identified as having reading difficulties, and the principal and parents as supporting informants. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions, and their validity was tested through triangulation of sources and techniques. The results of the study indicate that the initial reading ability of students with special needs is still low, especially in recognizing letters, pronouncing letter sounds, and combining syllables. Initial reading instruction is implemented in stages through the Individual Learning Program (PPI), with an emphasis on imitation and repetition methods and the use of simple media. The research conclusion confirms that the implementation of inclusive education that is humanistic, adaptive, and oriented towards individual needs is very important to support the success of early reading learning for students with dyslexia. Keywords: Inclusive education; Beginning reading; Dyslexia; Elementary school; Individualized learning Abstrak Pendidikan inklusif menuntut adanya layanan pembelajaran yang mampu mengakomodasi keberagaman kemampuan peserta didik, termasuk anak yang mengalami kesulitan membaca seperti disleksia. Permasalahan yang sering muncul di sekolah dasar penyelenggara pendidikan inklusif adalah rendahnya kemampuan membaca permulaan pada peserta didik berkebutuhan khusus di kelas rendah. Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan pembelajaran membaca permulaan dalam konteks pendidikan inklusif serta mengidentifikasi hambatan yang dialami peserta didik dengan disleksia. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Subjek penelitian meliputi peserta didik kelas awal sekolah dasar, guru kelas, peserta didik yang teridentifikasi mengalami kesulitan membaca, serta kepala sekolah dan orang tua sebagai informan pendukung. Teknik pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan studi dokumentasi. Data dianalisis dengan tahapan reduksi data, penyajian data, dan penarikan kesimpulan, serta diuji keabsahannya melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa kemampuan membaca permulaan peserta didik berkebutuhan khusus masih rendah, khususnya dalam mengenal huruf, melafalkan bunyi huruf, dan menggabungkan suku kata. Pembelajaran membaca permulaan dilaksanakan secara bertahap melalui Program Pembelajaran Individual (PPI), dengan penekanan pada metode peniruan dan pengulangan serta penggunaan media sederhana. Kesimpulan penelitian menegaskan bahwa penerapan pendidikan inklusif yang humanis, adaptif, dan berorientasi pada kebutuhan individual sangat penting untuk mendukung keberhasilan pembelajaran membaca permulaan bagi peserta didik dengan disleksia. Kata Kunci: Pendidikan inklusif; Membaca permulaan; Disleksia; Sekolah dasar; Pembelajaran individual